2018
DOI: 10.1111/jomf.12482
|View full text |Cite
|
Sign up to set email alerts
|

Crossing Boundaries: “Some College,” Schools, and Educational Assortative Mating

Abstract: As more Americans delay marriage and meet partners online, schools may be less important for educational assortative mating. At the same time, social ties formed during college may continue to shape partner choice later in adulthood. This study focuses on young adults with “some college, no degree” to see what, if any, marriage‐market benefit is gained from exposure to highly educated social networks in college. Using data from the National Longitudinal Study of Youth 1997, including newly collected postsecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
4
0
1
Order By: Relevance
“…When we used counterfactual approaches that compared high school and college graduates who were similar in backgrounds and early life health and skills, the college advantage remained evident for mental and global health, although not for physical domains. This finding corroborates the threshold effect: BA completion was repeatedly found to be associated with better outcomes than sub-BA levels across diverse life domains (Hout 2012; McClendon 2018), including health (J. B. Kane et al 2018; Lawrence et al 2018).…”
Section: Discussionsupporting
confidence: 80%
“…When we used counterfactual approaches that compared high school and college graduates who were similar in backgrounds and early life health and skills, the college advantage remained evident for mental and global health, although not for physical domains. This finding corroborates the threshold effect: BA completion was repeatedly found to be associated with better outcomes than sub-BA levels across diverse life domains (Hout 2012; McClendon 2018), including health (J. B. Kane et al 2018; Lawrence et al 2018).…”
Section: Discussionsupporting
confidence: 80%
“…Another finding is that partners who met through dating apps were more educationally exogamous than those who met elsewhere, particularly those who met through local networks of friends or associations, at school or at work. Especially for highly educated women marrying later in life and investing in professional careers (selectivity results show that app users are significantly more likely to experience work-life conflict, see S5.4 Table in S1 File), dating apps may effectively replace local dating pools and schools as key marriage markets [78]. It was also found that partnerships initiated on dating apps are not more exogamous on origin.…”
Section: Plos Onementioning
confidence: 95%
“…As a result, new sites have emerged that provide older singles with the opportunity to meet potential partners outside of more traditional meeting spots like the workplace or the neighbourhood, such as singles-only holidays and after-work parties. The expanded age range of the partnering market has also boosted the rise of online dating (McClendon 2018;Rosenfeld et al 2019).…”
Section: Needs Preferences Opportunitiesmentioning
confidence: 99%